Pengaruh Konseling Realitas Teknik Biblioterapi Terhadap Motivasi Belajar Siswa di MTsN 2 Kota Payakumbuh - Dwi Aanggre Arianti; Yuliana Nelisma; Ardimen Ardimen; Dasril Dasril (Universitas PGRI SUMATERA BARAT, 2022)
The purpose of this study was to examine the effect of reality counseling with bibliotherapy techniques on increasing student motivation at MTsN 2 Payakumbuh. This type of research is quantitative research using experimental methods. The design used in this study is a pre-experimental design with the type of one group pre-test and post-test design by measuring students' learning motivation using the same instrument in the pre-test and post-test measurements. The population in this study was class VII students, while the sample in this study were 12 students who had low learning motivation. The instrument used is the Likert model of learning motivation scale instrument. The technique used is random sampling. The results showed that there was a significant effect of reality counseling on bibliotherapy techniques on increasing student motivation at MTsN 2 Payakumbuh. The researcher recommends that counselors and Guidance and Counseling teachers be able to apply reality counseling with bibliotherapy techniques to student learning motivation.